The politics of cinematic realism during the Chinese Cultural Revolution, 1966-1976 - Lu, Bohua (Curtin University, 2013)
This thesis explores the politics of cinematic realism during the Chinese Cultural Revolution from 1966 to 1976. It examines the presentation and representation of the films produced and shown at that period to determine how they served the needs of the Communist Party and China, and examines the influence of the political leaders on film production. The thesis reveals the impact of the politics of cinematic realism in film production and the representation of historical events.